Crystals of salt - Lau, Wei Hong (Universiti Putra Malaysia Press, 2013)
The notorious armyworm is one of the most destructive leaf-feeding insect pests worldwide, which can defoliate many economically important crops. As suggested by its name, they emerge like a troop of army and can skeletonize the entire crop overnight. They burrow into the soil and form pupae. As the saying goes, every living creature has its own natural enemies. Aclose observation on armyworm dying naturally in the field may give us a clue to a solution to end the disaster brought by this notorious insect pest.